Synthesis and Anti-Tubercular Activity of 6-Substtitutedaryl-4-Arylidene- 4, 5-Dihydropyridazin-3(2H)-One Derivatives against Mycobacterium Tuberculosis: Anti-TB activity of some dihydropyridazin-3(2H)-ones - Asif, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2019)
Several 4-substituted-benzylidene-6-substituted-phenyl-4,5-dihydro-pyridazin-3(2H)-one derivatives (3a-q) were synthesized and evaluated for their antimicrobial activities with an aim to obtain promising antitubercular agents. In the first step, 6-aryl-2, 3, 4, 5-tetrahydro-pyridazin-3-ones (2) was prepared by reacting 4-aryl-4-oxobutanoic acids (1) with hydrazine hydrate. Then, aryl-aldehydes were reacted with compounds 2 to furnish pyridazinones (3a-q). Finally, the synthesized compounds were evaluated for their in vitro antitubercular activities against mycobacterium strains and compared to reference drugs streptomycin (MIC value of 6.25μg/mL) and pyrizinamide (MIC value of 3.125μg/mL). Compound 3m and 3n was found to have most significant action. Identity of these compounds was ascertained using IR, NMR and mass spectral data results.